THE INFLUENCE OF SELF-EFFICACY, SOFT SKILLS, AND FIELD WORK PRACTICE PROGRAMS ON WORK READINESS OF BUSINESS SERVICE OFFICE MANAGEMENT STUDENTS OF SMK NEGERI 10 JAKARTA - Wibowo, Sarah Savira; Marsofiyati , Marsofiyati; Wolor , Christian Wiradendi (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of self-efficacy, soft skills, and field work practice programs on the work readiness of business service office management students of SMK Negeri 10 Jakarta. This study uses descriptive quantitative methods. The population in this study amounted to 216 students of the Business Services Office Management Department of SMK Negeri 10 Jakarta. The technique in determining the sample in this study used proportional random sampling so that the sample in this study amounted to 140 students. Data were collected through questionnaires and data analysis was carried out using the help of Smart PLS. The results in this study indicate that Self-Efficacy has a positive and significant effect on Work Readiness, Soft Skills have a positive and significant effect on Work Readiness, and the Field Work Practice Program has a positive and significant effect on Work Readiness in Business Services Office Management Department Students of SMK Negeri 10 Jakarta.